2013
DOI: 10.1016/j.ijid.2013.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Mortality indicators in community-acquired pneumonia requiring intensive care in Turkey

Abstract: SCAP requiring ICU admission is associated with considerable mortality for ICU patients. Increased awareness appears essential for the microbiological diagnosis of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
(40 reference statements)
2
8
0
2
Order By: Relevance
“…Patients with severe respiratory failure due to CAP and previous cardiac or respiratory disease usually have a better response to NIV than patients with de novo acute respiratory failure (as demonstrated in previous studies) ( 2 , 18 , 19 ). Few studies have investigated the benefits of NIV in patients with severe CAP: the oldest showed good results principally in patients with chronic obstructive pulmonary disease (COPD) and hypercapnic respiratory failure ( 18 ).…”
Section: Discussionsupporting
confidence: 54%
“…Patients with severe respiratory failure due to CAP and previous cardiac or respiratory disease usually have a better response to NIV than patients with de novo acute respiratory failure (as demonstrated in previous studies) ( 2 , 18 , 19 ). Few studies have investigated the benefits of NIV in patients with severe CAP: the oldest showed good results principally in patients with chronic obstructive pulmonary disease (COPD) and hypercapnic respiratory failure ( 18 ).…”
Section: Discussionsupporting
confidence: 54%
“…Even considering the design of our study, which excluded surgical ICU admissions, half of the CA infection patients had any type of trauma history. Accordingly, considering the one-third to one-half mortality rates for the CA pneumonias in the ICUs, [19][20][21][22][23] the mortality was exceedingly high (59.5%) in our patients. The high number of trauma patients (n = 21) as well as severity of illness (APACHE II scores average = 23) may be affected mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated in intensive care or admitted with severe pneumonia have mortality ranging from 20% to 50% depending on the report. [ 60 61 62 ] The strategies to reduce mortality include respiratory support, antibiotics, and adjuvant therapies.…”
Section: Resultsmentioning
confidence: 99%
“…[ 65 ] Noninvasive ventilation (NIV) is associated with reduced mortality, although no randomized controlled trials exist. [ 59 60 61 ] A total of 40 patients admitted to the ICU with acute hypoxemic respiratory failure but not immediately intubated were trailed on NIV, and 47.6% of those patients subsequently required intubation. For a group largely composed of acute respiratory distress syndrome patients, NIV had a high failure rate.…”
Section: Resultsmentioning
confidence: 99%